Chapter Developing Active Citizenship Through Adult Learning and Education. Experiences from an INTALL Winter School Comparative Working Group - Nemeth, Balazs (Studies on Adult Learning and Education, 2020)
Active citizenship became a research issue for adult learning and education in 1995 when the Council of Ministers decided to make 1996 the Year of Lifelong Learning. Moreover, the Lisbon programme, in the year 2000, reinforced the relevance of the issue and, along with employability, connected it to lifelong learning. That is why since 2001 comparative adult learning and education researchers have put a specific focus on analysing active citizenship and bridging it to adult learning. For this very reason, a distinguished Comparative Working Group was formed at the 2019 Winter School of the Erasmus+ Intall project-on the one hand, to collect different national/regional and local narratives and understandings of active citizenship and, on the other, to gather examples, good practices, formations of active citizens, or trajectories of how to learn for active citizenship as routes and processes of lifelong learning. The same Winter School comparative group tried to analyse the similarities and differences collected in an effort to relate them to existing theoretical frames offered by key authors on the topic, including Baert, Jansen, Jarvis, Johnston, Wildemeeersch, and others. This paper discusses the experiences of the comparative working group and formulates some special conclusions and comments for further actions of comparative studies in adult learning and education.